2020
DOI: 10.1016/j.heliyon.2020.e04549
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeophysical and aquifer vulnerability zonation of a typical basement complex terrain: A case study of Odode Idanre southwestern Nigeria

Abstract: An approach engaging Vertical Electrical Sounding (VES) and remote sensing data was carried out with a view to developing groundwater potential and aquifer vulnerability maps of the study area. One hundred and one (101) depth sounding data were acquired using Schlumberger array, with half maximum current electrode separation (AB/2) of 100 m. The VES were quantitatively interpreted using partial curve matching and computer aided iteration to determine the geoelectrical parameters of each station. The remote sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…The Southeastern part of the area is dominated by low aquifer thickness ranging between 0.91 -10 m (Fig. 5g), but majority of the aquifer exceed a thickness of 11 m. Publications of groundwater potentiality within similar geology Akintorinwa et al (2020) reported that thicknesses within this range are considerable as good groundwater potential for domestic use.…”
Section: Aquifer Thicknessmentioning
confidence: 97%
See 2 more Smart Citations
“…The Southeastern part of the area is dominated by low aquifer thickness ranging between 0.91 -10 m (Fig. 5g), but majority of the aquifer exceed a thickness of 11 m. Publications of groundwater potentiality within similar geology Akintorinwa et al (2020) reported that thicknesses within this range are considerable as good groundwater potential for domestic use.…”
Section: Aquifer Thicknessmentioning
confidence: 97%
“…The concept of Analytical Hierarchy Process (AHP) techniques was developed by Thomas Saaty in the 1970 as an appropriate approach to quantify weights for multi-criteria decision analysis (MCDA). Expert's opinions from publication (Akintorinwa et al 2020) were sought on the relative importance of the aforementioned GPP's variables regarding the area underlain aquifer unit formation groundwater potentiality degree. The expert weights were provided to different GPPs considered and further calibrated using Saaty's scale ranging from 0 -9 (Saaty and Vargas 1991).…”
Section: The Mcda-ahp Model's Theory Utilizedmentioning
confidence: 99%
See 1 more Smart Citation
“…These characterized ranges of values coincide with the range of values for Log K & , as suggested by Van Stempvoort et al[40], which measures AVI by hydraulic resistance.Hence, the aquifer zones were classified by the AVI into poor/weak and moderate APC, with extremely high vulnerability and high vulnerability as presented in Table5. These results suggest that the Araromi area of Akungba-Akoko has poor/weak to moderate APC with extremely high AVI and high AVI, respectively, due to the generally thin overburden soil material cover and low hydraulic resistance, e.g.,[3,46]. Protective layers with suitable thickness and low hydraulic conductivity provide effective groundwater protection, resulting in a long residence time for infiltrating water.…”
mentioning
confidence: 99%
“…These characterized ranges of values coincide with the range of values for Log K 𝑅𝑅 , as suggested by Van Stempvoort et al[40], which measures AVI by hydraulic resistance.Hence, the aquifer zones were classified by the AVI into poor/weak and moderate APC, with extremely high vulnerability and high vulnerability as presented in Table5. These results suggest that the Araromi area of Akungba-Akoko has poor/weak to moderate APC with extremely high AVI and high AVI, respectively, due to the generally thin overburden soil material cover and low hydraulic resistance, e.g.,[3,46]. Protective layers with suitable thickness and low hydraulic conductivity provide effective groundwater protection, resulting in a long residence time for infiltrating water.…”
mentioning
confidence: 99%